Temporal Physiologic Profiles Associated with Return of Spontaneous Circulation in a Swine Model of Cardiopulmonary Resuscitation - Barbara Fyntanidou; Eirini Oloktsidou; Katerina Kotzampassi; Marios G. Bantidos; Christos Kofos; Andreas S. Papazoglou; Georgios Kazakos; Aikaterini Apostolopoulou; Athina Nasoufidou; Alexandra Arvanitaki; Maria Fasoula; Efstratios Karagiannidis; et al. (Journal of Clinical Medicine, 2026)
Background: Physiology-guided cardiopulmonary resuscitation (CPR) is increasingly recognized as a strategy to move beyond mechanical targets, but evidence remains limited and dominated by isolated metrics. We characterized multimodal physiologic profiles associated with return of spontaneous circulation (ROSC) in a swine model. Methods: We analyzed 24 swine undergoing standardized cardiac arrest followed by CPR. Variables included end-tidal carbon dioxide (ETCO2), systolic arterial pressure (SAP), diastolic arterial pressure (DAP), right ventricular systolic pressure (RVSP), carotid artery blood flow, stroke volume, and cerebral regional oxygen saturation. The primary early analysis used per-animal medians from minutes 1–5 of CPR, before any animal achieved ROSC. Later prespecified 5 min windows were evaluated exploratorily because they increasingly included post-ROSC measurements. A pre-ROSC sensitivity analysis, correlation analysis, and exploratory principal component analysis (PCA) with bootstrap assessment of loading stability were also performed. Results: Nine animals (37.5%) achieved ROSC, with a median time to ROSC of 10 min (range 6–18 min). During minutes 1–5, before any ROSC occurred, animals subsequently achieving ROSC had higher carotid flow, DAP, ETCO2, right ventricular pressure signal, and SAP; all differences remained significant after false discovery rate correction. In the pre-ROSC sensitivity analysis, ETCO2, SAP, DAP, right ventricular pressure signal, carotid flow, and stroke volume differed between animals subsequently achieving ROSC and those that did not (all p < 0.001), whereas cerebral regional oxygen saturation did not (p = 0.474). Later analytical windows increasingly included post-ROSC measurements and were therefore interpreted exploratorily. PCA summarized the shared early physiologic variation, with PC1 explaining 69.8% of variance; bootstrap analysis showed consistent positive contributions of the included variables to PC1. Conclusions: Successful resuscitation was associated with a distinct pressure–flow–gas-exchange profile during early and pre-ROSC CPR. These findings support further investigation of multimodal physiology-guided resuscitation.